Reactive Oxygen Species Scavenging Nanomedicine for the Treatment of Ischemic Heart Disease. Issue 35 (28th July 2022) - Zhang, Zhan; Dalan, Rinkoo; Hu, Zhenyu; Wang, Jiong‐Wei; Chew, Nicholas WS; Poh, Kian‐Keong; Tan, Ru‐San; Soong, Tuck Wah; Dai, Yunlu; Ye, Lei; Chen, Xiaoyuan
Abstract: Ischemic heart disease (IHD) is the leading cause of disability and mortality worldwide. Reactive oxygen species (ROS) have been shown to play key roles in the progression of diabetes, hypertension, and hypercholesterolemia, which are independent risk factors that lead to atherosclerosis and the development of IHD. Engineered biomaterial‐based nanomedicines are under extensive investigation and exploration, serving as smart and multifunctional nanocarriers for synergistic therapeutic effect. Capitalizing on cell/molecule‐targeting drug delivery, nanomedicines present enhanced specificity and safety with favorable pharmacokinetics and pharmacodynamics. Herein, the roles of ROS in both IHD and its risk factors are discussed, highlighting cardiovascular medications that have antioxidant properties, and summarizing the advantages, properties, and recent achievements of nanomedicines that have ROS scavenging capacity for the treatment of diabetes, hypertension, hypercholesterolemia, atherosclerosis, ischemia/reperfusion, and myocardial infarction. Finally, the current challenges of nanomedicines for ROS‐scavenging treatment of IHD and possible future directions are discussed from a clinical perspective. Abstract : The current developments, achievements, challenges, and future directions of reactive oxygen species (ROS)‐scavenging nanomedicine for the treatment of ischemic heart disease (IHD), as well as their risk factors, are reviewed. The properties, generation, and physiological roles of ROS in the process of IHD development and progression are discussed.